Factors Associated with Breastfeeding Practice among Mothers in Jazan City, Saudi Arabia - alzughbi, Najat Nasser; Mahmood, Syed Zafar; Sani, Mubarack (Journal of medical and pharmaceutical sciences, 2018)
Objective: To evaluate breastfeeding practice as well as to identify the factors that influence mothers decision to practice exclusive breastfeeding. Subjects and methods: This is a cross sectional study carried out from March 2017 to Jun 2018. Questionnaires were administrated to mothers who attended well baby clinics in primary health centers in jazan city. Results: The study included 400 women with age range from 17 to 49 years. Their children age ranged between 1 and 36 months. Most of the participants were Housewife (67.8%) and 47.8% of them were certified with university degree. Most of women had full term babies (92%), delivered normally (76%), gave mixed feeding for their babies (76%), did not use the pacifier (81%) and initiated first fed within one hour after delivery 54% that was derived from the breast in 75 %. The majority of the study group was healthy (90%) and majority of their children were healthy (95.5%).The most prevalent reasons for breast feeding (BF) were awareness about the importance of BF (50.4%) and advice of a family and/or mother (33.8%). The most prevalent reasons for artificial milk feeding were awarded artificial milk before delivery (26.8%), advice from relatives (24.7%), mother’ belief that artificial milk is good like breast milk (23.2%), and artificial milk awarded from the hospital during delivery (11.9%).The majority of mothers were satisfied with breast feeding (92%). Conclusion: Mixed feeding is a common practice among women in Jazan while exclusive breast feeding was practiced by a proportion consistent with the WHO target proportion less than six months.